2001
DOI: 10.1094/pdis.2001.85.5.506
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Resistance Genes Effective Against Rice Bacterial Blight Pathogen in Eastern India

Abstract: Breeding for bacterial blight resistance in rice requires an understanding of the contemporary pathogen populations in the locations where resistance genes are to be deployed. We characterized 450 strains of Xanthomonas oryzae pv. oryzae collected from three states of India using polymerase chain reaction fingerprinting and virulence analysis. This pathogen collection was differentiated into 17 haplotypes (12 lineages at 80% similarity level). Significant differences in the distribution of haplotypes were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 16 publications
8
41
0
1
Order By: Relevance
“…PXO99 was identified during the 1980s as Philippine Xoo race 6 (Khush and Angeles, 1999), and xa13 was first discovered as a resistant allele against PXO99 in Indian rice variety BJ1 (Ogawa et al, 1987). IRBB13 carrying xa13 is resistant to >50% of Xoo strains/isolates collected from major rice-growing areas of China and India (Shanti et al, 2001;Singh et al, 2003;Li et al, 2009). These results suggest that Xoo strains, which overcome rice by activating Xa13, may have become the dominant pathogens in at least China and India.…”
Section: Discussionmentioning
confidence: 99%
“…PXO99 was identified during the 1980s as Philippine Xoo race 6 (Khush and Angeles, 1999), and xa13 was first discovered as a resistant allele against PXO99 in Indian rice variety BJ1 (Ogawa et al, 1987). IRBB13 carrying xa13 is resistant to >50% of Xoo strains/isolates collected from major rice-growing areas of China and India (Shanti et al, 2001;Singh et al, 2003;Li et al, 2009). These results suggest that Xoo strains, which overcome rice by activating Xa13, may have become the dominant pathogens in at least China and India.…”
Section: Discussionmentioning
confidence: 99%
“…The successful pyramiding of disease resistance genes or resistance QTLs and the effectiveness of this strategy has been reported for example for stripe rust (Castro et al 2003) or barley yellow mosaic virus resistance (Okada et al 2004, Werner et al 2005 in barley, leaf rust (Kloppers and Pretorius 1997) or powdery mildew resistance (Liu et al 2000) in wheat, as well as leaf blast (Hittalmani et al 2000) or bacterial blight resistance (Shanti et al 2001;Singh et al 2001) in rice.…”
Section: Diagnostic Molecular Markersmentioning
confidence: 99%
“…DNA fingerprinting and pathotype analysis have indicated that there is a significant amount of diversity within populations of Xoo in India and other rice growing countries (Adhikari et al 1995;Yashitola et al 1997;Shanti et al 2001;Gupta et al 2001;Singh et al 2003). A number of near-isogenic rice lines in the genetic background of IR24 were inoculated with Indian strains of Xoo and those containing the single resistance genes Xa21, xa13 and xa5 were found to provide moderate to strong levels of resistance (Goel et al 1998;Shanti et al 2001;Joseph et al 2004;our unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…A number of near-isogenic rice lines in the genetic background of IR24 were inoculated with Indian strains of Xoo and those containing the single resistance genes Xa21, xa13 and xa5 were found to provide moderate to strong levels of resistance (Goel et al 1998;Shanti et al 2001;Joseph et al 2004;our unpublished results). PCR based molecular markers that are tightly linked to each of these three resistance genes have been developed (Ronald et al 1992;Yoshimura et al 1995;Zhang et al 1996) and used to pyramid them into the genetic background of different rice varieties (Huang et al 1997;Sanchez et al 2000;Singh et al 2001;Joseph et al 2004).…”
Section: Introductionmentioning
confidence: 99%